Modeling the electrical resistivity of polymer composites with segregated structures - Sung-Hoon Park (Nature Portfolio, 2019)
Carbon nanotube–polymer composites containing secondary fillers are thought to possess enhanced electrical and mechanical properties. Here the authors combine Monte Carlo calculations with resistivity experiments to study the effect of filler size and shape on electrical conductivity.